Differential effects of recent versus past traumas on mood, social support, binge drinking, emotional eating and BMI, and on neural responses to acute stress. (2nd November 2021) - Hermes, Gretchen; Fogelman, Nia; Seo, Dongju; Sinha, Rajita
Abstract: Traumatic stress is associated with risk of psychiatric and physical illnesses. However, the differential and separable effects of past versus recent traumas on maladaptive coping and neural responses are not known. We conducted two studies to assess separate and combined effects of cumulative recent and past trauma on health outcomes (study 1) and on neural responses to acute stress exposure in a subsample of individuals (study 2). Study 1 assessed a large cohort of 677 community adults cross-sectionally, and findings indicated that both high recent (within the last 12 months) and past trauma (prior to the last twelve months) were associated with more physical and psychological symptoms, including increased depression (all p 's < .05). However, recent trauma alone was associated with higher problematic alcohol use, a greater maximum number of alcohol drinks consumed, greater emotional eating scores, higher state and trait anxiety scores, and poorer lifestyle habits (all p 's < .05). Past trauma alone was associated with higher BMI, decreased social support, and a lower average cortisol relative to ACTH ratio (all p 's < .02). Study 2 involving a functional brain scan on a subsample ( N = 75) indicated greater recent trauma was associated with a hyperactive response in the ventromedial prefrontal cortex (VmPFC) to neutral-relaxed exposure, but blunted VmPFC response to acute stress exposure ( p < .05: whole brain corrected-WBC). By contrast, high past trauma was associated with a hyper-sensitized neural response to stress in the cortico-limbic-striatal regions ( p < .05, WBC) critical for reward and emotion processing. Together, these findings suggest differential neurobehavioral and health effects of cumulative past versus recent trauma exposure.